Good long-term functional outcomes after rotationplasty despite osteoarthritis in the (pseudo)knee - G.G.J. Krebbekx; F.F. Smithuis; M.J.C. Duivenvoorden; R. Hemke; I.N. Sierevelt; G.R. Schaap; J.A.M. Bramer; G.M.M.J. Kerkhoffs; F.G.M. Verspoor (Osteoarthritis and Cartilage Open)
Objective: Rotationplasty is a surgical procedure primarily performed in patients with malignancies around the knee. Altered gait mechanics after surgery, such as reduced flexion of the (pseudo)knee and ipsilateral hip and changes in ground reaction forces, may predispose patients to osteoarthritis (OA) in the lower extremities. This study evaluated the long-term prevalence of OA and its association with pain and daily functioning. Method: Rotationplasty survivors who underwent surgery between 1980 and 2002 in Amsterdam received radiographic assessment of the (pseudo)knee, contralateral ankle, and both hips (weight-bearing mortise, lateral and AP views). OA was graded using the Kellgren-Lawrence scale. Functional outcomes, pain, quality of life, and sports participation were evaluated with the FAOS, AOFAS, and Harris Hip Score questionnaires. Statistical analyses included t-tests, Mann-Whitney U, chi-square, and Fisher's exact tests. Results: Thirty patients (mean age 49.4 ​± ​9.2 years; mean follow-up 32.4 ​± ​4.6 years) participated. Moderate-to-severe OA was found in 43 ​% of ipsilateral (pseudo)knees, 10 ​% of contralateral ankles, 33 ​% of ipsilateral hips, and 11 ​% of contralateral hips. Osteophytes were most common in the anterior tibial and subtalar regions (20 ​%), and joint space narrowing was most frequent in the subtalar (20 ​%) and medial tibiotalar (13 ​%) regions. Functional scores were generally favorable. The presence of osteoarthritis in the pseudo-knee was significantly associated with longer follow-up time. Conclusion: Functional outcomes after rotationplasty are well preserved over time, despite a higher prevalence of osteoarthritis in the (pseudo)knee compared to the contralateral ankle as a long-term consequence of the procedure.